PEMBERDAYAAN MASYARAKAT INDRALAYA RAYAMELALUI INTRODUKSI TEKNOLOGI SOLAR DRYING BIJI LOTUS (Nelumbo nucifera) LIAR - sherly ridhowati (STMIK Royal, 2024)
The use of natural water resources in the surrounding area must be utilized optimally through local source diversification activities, especially in Indralaya Raya village, Indralaya District, Ogan Ilir Regency. Availability of lotus seeds is abundant especially during rainy season but has not been utilized optimally. In services program, the introduction of solar drying technology was carried out through outreach and assistance to Village residents, especially youth organizations and micro small medium enterprises (UMKM), regarding the application of technology used for the drying process of lotus seeds, so that the dried lotus seeds could be stored longer for further used, then the next activity continued with the processing of diversified flour products and their derivatives. The success of this activity has shown that the Indralaya Raya residents were enthusiastic about this service activity as shown by the activity achievement indicators. Socialization and assistance activities on the use of solar-powered dryers and the manufacture of flour products and their derivatives have had a positive impact on the Indralaya Raya village community in empowering the activities of youth organizations and UMKMs.